Monitoring środowiska jako podstawowe źródło danych środowiskowych - Sej-Kolasa, Małgorzata (Monitoring System for Environment as the Basic Source of Environmental Data, 2005)
Environmental data should be collected within a uniform system, organised and coordinated by a competent body or institution. In Polish conditions, an instrument to secure reliable data on the state of environment is the National Monitoring System for Environment (PMŚ).The article points out the major role of the state system for environment monitoring in collection, storage and distribution of environmental data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 137-152